The concept and participants of the insurance relationship (Journal of actual problems of jurisprudence, 2019)
The article considers the concept of insurance relationship. As well as the legal status of their participants. Insurance relations, being settled legal norms that are in the form of insurance relations. Characteristics of the insurance relations, of course, complicated bythe fact that the insurance law is complex, due to which the insurance legal relations are presented fairly heterogeneous, and signi fi cantlydifferent from each other kinds of relations: civil law and administrative law. The insurance relationship is a relationship, protected bythe state. This position is determined fi rst of all by the fact that the state seeks to ensure the application of the provisions of the norms ofthe insurance legislation, issued by the state and which expressed his will. Ensuring the implementation of the norms of the insurancelaw, the state shall protect and regulated by the rules of insurance relations. me